Let u , v , w be real numbers satisfying u v w = u + v + w = 1 and u 2 + v 2 + w 2 = 2 0 1 3 . If u v + w 1 + w u + v 1 + v w + u 1 = − b a , where a and b are positive coprime integers, what is the value of a ?
This problem is posed by Christyan Tamaro N .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice job! A very clear and well written solution.
The initial observation that u v + w = u v − u − v + 1 = ( u − 1 ) ( v − 1 ) helps to save a lot of tedious calculation.
Squaring the equation u + v + w = 1 , we get
u 2 + v 2 + w 2 + 2 u v + 2 u w + 2 v w = 1 .
Then 2 0 1 3 + 2 ( u v + u w + v w ) = 1 , so u v + u w + v w = − 1 0 0 6 .
We can then write u v + w 1 + w u + v 1 + v w + u 1 = u v + w ( u + v + w ) 1 + w u + v ( u + v + w ) 1 + v w + u ( u + v + w ) 1 = u v + u w + v w + w 2 1 + u v + u w + v 2 + v w 1 + u 2 + u v + u w + v w 1 = ( u + w ) ( v + w ) 1 + ( u + v ) ( v + w ) 1 + ( u + v ) ( u + w ) 1 = ( u + v ) ( u + w ) ( v + w ) ( u + v ) + ( u + w ) + ( v + w ) = ( u + v ) ( u + w ) ( v + w ) 2 ( u + v + w ) .
Since u + v + w = 1 , this is equal to ( 1 − w ) ( 1 − v ) ( 1 − u ) 2 = 1 − ( u + v + w ) + ( u v + u w + v w ) − u v w 2 = 1 − 1 − 1 0 0 6 − 1 2 = − 1 0 0 7 2 .
The final answer is 2.
Nice job! Great solution and and presentation.
(u+v+w)^2= u^2+v^2+w^2 +2(uv+vw+wu) and we get uv+vw+wu=-1006 u=1-v-w v=1-u-w w=1-u-v so, we get the given expression as 1/(u-1)(v-1) + 1/(v-1)(w-1) + 1/(w-1)(u-1) which is equal to (u-1+v-1+w-1)/(u-1)(v-1)(w-1) = (u+v+w-3)/(uvw-1-uv-vw-wu+u+w+v)= -2/1007 by substituting the values and hence a=2
Nice solution!
Let $$S = \sum {\text{cyc}} \frac{1}{uv + w}$$ Now because u v w = 1 we get $$S = \sum {\text{cyc}} \frac{1}{\frac{1}{u} + u} = \sum {\text{cyc}} \frac{u}{u^2 + 1}$$ Adding the fractions we get $$S = \bigg(\sum {\text{sym}} u^2v + \sum {\text{cyc}} u^2v^2w + \sum {\text{cyc}} u\bigg)\Bigg/ \bigg(u^2v^2w^2 + \sum {\text{cyc}} u^2v^2 + \sum {\text{cyc}} u^2 + 1\bigg) = \frac{A}{B}$$ Let's compute A and B individually. Now $$\left(\sum {\text{cyc}} u\right)^2 = 1 = \sum {\text{cyc}} (u^2 + 2uv) = 2013 + 2\sum {\text{cyc}} uv$$ Hence $$\sum {\text{cyc}} uv = -1006$$ Now $$\sum {\text{cyc}} u^2v^2w = uvw\sum {\text{cyc}} uv = -1006$$ $$\sum {\text{sym}} u^2v = \left(\sum {\text{cyc}}u\right)\left(\sum {\text{cyc}} uv\right) - 3uvw = 1 \cdot (-1006) - 3 = -1009$$ So $$A = -1009 - 1006 + 1 = -2014$$ Also $$\left(\sum {\text{cyc}} uv\right)^2 = (-1006)^2 = \sum {\text{cyc}} u^2v^2 + 2uvw\sum {\text{cyc}}u = \sum {\text{cyc}}u^2v^2 + 2$$ Hence $$\sum {\text{cyc}} u^2v^2 = (-1006)^2 - 2 = 1012034$$ Hence $$B = 1 + 1012034 + 2013 + 1 = 1014049$$ Hence $$-\frac{a}{b} = \frac{A}{B} = \frac{2014}{1014049} = \frac{2}{1007}$$ So $$a = \boxed{2}$$
for B ther's no need of calculating the entire value u can just insert the above sigma value in B and by rearranging it we can get it in the form of "(a^2+2ab+b^2)" which gives us (1006+1)^2 = 1007^2...I think thats much easier way 2 approach.......
I did the hard long way like this too... sigh
Notice that u v w = = = 1 − v − w 1 − u − w 1 − u − v
Subtitute these values. u v + w 1 + w u + v 1 + v w + u 1 = = = = = = u v + ( 1 − u − v ) 1 + w u + ( 1 − u − w ) 1 + v w + ( 1 − v − w ) 1 ( u − 1 ) ( v − 1 ) 1 + ( w − 1 ) ( u − 1 ) 1 + ( v − 1 ) ( w − 1 ) 1 ( u − 1 ) ( v − 1 ) ( w − 1 ) ( w − 1 ) + ( v − 1 ) + ( u − 1 ) u v w − u v − u w − v w + u + v + w − 1 ( u + w + v ) − 3 u v w − ( u v + u w + v w ) + ( u + v + w ) − 1 1 − 3 1 − ( u v + u w + v w ) + 1 − 1 − 2
How to find u v + u w + v w ? Use the equations given in the problem! u + v + w = u v w = 1 u 2 + v 2 + w 2 = 2 0 1 3
Square u + v + w , and see what would we have.
( u + v + w ) 2 1 2 1 = = = u 2 + v 2 + w 2 + 2 u v + 2 u w + 2 v w ( u 2 + v 2 + w 2 ) + 2 ( u v + u w + v w ) 2 0 1 3 + 2 ( u v + u w + v w )
We get u v + u w + v w = 2 1 − 2 0 1 3 = − 1 0 0 6 .
Now, let's return to the equation we left. 1 − ( u v + u w + v w ) + 1 − 1 − 2 = = 1 − ( − 1 0 0 6 ) + 1 − 1 − 2 1 0 0 7 − 2
So, our answer is 2 .
u v w = 1 u + v + w = 1
⇒ u 2 + v 2 + w 2 + 2 ∑ u v = 1 ⇒ ∑ u v = − 1 0 0 6 .
Now ,
u v + w = u v + 1 − u − v = ( u − 1 ) ( v − 1 ) .
Similarly,
w u + v = ( w − 1 ) ( u − 1 ) , and
v w + u = ( v − 1 ) ( w − 1 )
Now ,
u v + w 1 + w u + v 1 + v w + u 1
= ( u − 1 ) ( v − 1 ) 1 + ( w − 1 ) ( u − 1 ) 1 + ( v − 1 ) ( w − 1 ) 1
= ( u − 1 ) ( v − 1 ) ( w − 1 ) u + v + w − 3 = ( u − 1 ) ( v − 1 ) ( w − 1 ) − 2
( u − 1 ) ( v − 1 ) ( w − 1 ) = u v w − ( u + v + w ) − ∑ u v − 1
= 2007).
Hence , the sum becomes 2 0 0 7 − 2 and hence a = 2
Note : I found a small mistake in the question , u , v and w can not be all reals. They are roots of equation :
x 3 − x 2 − 1 0 0 6 x − 1 = 0 , which has only one real root .
I am sorry for the last statement . Actually, i checked at wolfram , you can also check , it shows − 3 1 . 2 2 1 + 0 . × 1 0 − 4 i , which at a glance looks imaginary.
Algebra is a place where some expressions fit in miraculously better than others.
Observe that: u v + w 1 = u v + 1 − u − v 1 = ( u − 1 ) ( v − 1 ) 1 and the like. So the expression becomes:
( u − 1 ) ( v − 1 ) 1 + ( u − 1 ) ( w − 1 ) 1 + ( w − 1 ) ( v − 1 ) 1 which on evaluating gives ( u − 1 ) ( v − 1 ) ( w − 1 ) u + v + w − 3 . . . . . . . . . . . . . ( ∗ )
Also, u v + v w + u w = 2 1 ( ( u + v + w ) 2 − ( u 2 + v 2 + w 2 ) ) = − 1 0 0 6
Expanding the denominator of ( ∗ ) ,& substituting values, we get the expression as − 1 0 0 7 2 , with a = 2 .
Problem Loading...
Note Loading...
Set Loading...
Note that u v + w = u v − u − v + 1 = ( u − 1 ) ( v − 1 ) . Thus, the desired sum is ( u − 1 ) ( v − 1 ) 1 + ( v − 1 ) ( w − 1 ) 1 + ( w − 1 ) ( u − 1 ) 1 = ( u − 1 ) ( v − 1 ) ( w − 1 ) u − 1 + v − 1 + w − 1 = u v w − u v − v w − w u + u + v + w − 1 u + v + w − 3 = 1 − u v − v w − w u − 2 . From the identity ( u + v + w ) 2 = u 2 + v 2 + w 2 + 2 ( u v + v w + w u ) , it follows that u v + v w + v u = 2 1 2 − 2 0 1 3 = − 1 0 0 6 . Thus, the sum is equal to − 1 0 0 7 2 , so the numerator is equal to 2 .